If we knew then what we know now: The preparedness experience of pre-loss and post-loss dementia caregivers. Issue 2 (7th February 2022) - Supiano, Katherine P.; Luptak, Marilyn; Andersen, Troy; Beynon, Cynthia; Iacob, Eli; Wong, Bob
Abstract: We evaluated the relationship between grief preparedness and grief experience in 106 family caregivers anticipating or who had experienced the death of a family member with dementia. Using a phenomenological lens to discern a process of meaning-making in narratives, we found preparation that included positive construction of memories, death as the end of suffering, relationship resolution, and shared construction of meaning were associated with positive grief. Those caregivers who experienced the family member's decline as traumatic, caregiver role loss, unavailable support, and difficulties creating a new life reported inadequate death preparation, and difficulty making meaning of the illness and death.